2019
DOI: 10.1155/2019/9671206
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Functions of Mesenchymal Stem Cells in Tissue Engineering

Abstract: The inflammatory response to chronic injury affects tissue regeneration and has become an important factor influencing the prognosis of patients. In previous stem cell treatments, it was revealed that stem cells not only have the ability for direct differentiation or regeneration in chronic tissue damage but also have a regulatory effect on the immune microenvironment. Stem cells can regulate the immune microenvironment during tissue repair and provide a good “soil” for tissue regeneration. In the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 151 publications
0
74
0
Order By: Relevance
“…Although cell replacement is an essential component of MSC-based therapy, their therapeutic effect is mainly due to their immunomodulatory functions. Stem cells can regulate the immune microenvironment during tissue repair and provide a good "soil" for tissue regeneration (Li et al, 2019). Such definition and characterization is important to be performed as they ensure a standardization process which would allow comparison across multiple studies and could facilitate potential clinical (Mendicino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although cell replacement is an essential component of MSC-based therapy, their therapeutic effect is mainly due to their immunomodulatory functions. Stem cells can regulate the immune microenvironment during tissue repair and provide a good "soil" for tissue regeneration (Li et al, 2019). Such definition and characterization is important to be performed as they ensure a standardization process which would allow comparison across multiple studies and could facilitate potential clinical (Mendicino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…58) Moreover, the effects of the material, porosity, and hardness of scaffolds on MSCs require further study. 59) In conclusion, 3D MSCs can restore the number of platelets by upregulating immune regulation and ECM expression and therefore have promising therapeutic efficacy in ITP. The MSCs and 3D MSCs can reverse this trend, especially in the 3D MSC group.…”
Section: Discussionmentioning
confidence: 89%
“…Bone engineering makes refractory bone defect reconstruction feasible and the key lies in the selection of seed cells . Multiple studies have demonstrated that SMSCs possess the extensive proliferative ability and multilineage differentiation potential .…”
Section: Discussionmentioning
confidence: 99%
“…Bone engineering makes refractory bone defect reconstruction feasible and the key lies in the selection of seed cells. 31,32 Multiple studies have demonstrated that SMSCs possess the extensive proliferative ability and multilineage differentiation potential. 33,34 Our current study demonstrated that SMSCs were similar to other stem cells in terms of immunophenotypes and could be differentiated into osteoblasts in vitro.…”
Section: Discussionmentioning
confidence: 99%